2005
DOI: 10.1056/nejmra041720
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Lymphocytic Leukemia

Abstract: B-cell chronic lymphocytic leukemia (B-CLL) has long been considered a disease of "accumulation," due to a presumed defect in programmed cell death. Recent data, however, suggest that B-CLL cells are born at a normal to an accelerated rate, with the rate of proliferation varying among patients. In addition, differences in birth rates, activation state, and inducibility appear to exist among subpopulations of cells within individual leukemic clones. The extent to which such dissimilarities influence clinical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
818
0
43

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,441 publications
(893 citation statements)
references
References 122 publications
10
818
0
43
Order By: Relevance
“…MicroRNA 15a/16 -1 deregulation, through deletion or mutation, affects tumor resistance to apoptosis, by causing Bcl2 overexpression (37). It has been reported that the locus corresponding to microRNA 15a and microRNA 16 -1 at 13q14 is deleted in more than half of B-cell chronic lymphocytic leukemias (34,35). The undeleted microRNA 15a-microRNA 16 -1 allele, in chronic lymphocytic leukemia patients, may also contain inactivating point mutations (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA 15a/16 -1 deregulation, through deletion or mutation, affects tumor resistance to apoptosis, by causing Bcl2 overexpression (37). It has been reported that the locus corresponding to microRNA 15a and microRNA 16 -1 at 13q14 is deleted in more than half of B-cell chronic lymphocytic leukemias (34,35). The undeleted microRNA 15a-microRNA 16 -1 allele, in chronic lymphocytic leukemia patients, may also contain inactivating point mutations (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic lymphocytic leukemia (CLL) is a malignancy of mature, antigen-experienced B lymphocytes that are highly proliferative [15]. Due to their uncontrolled growth, B-CLL cells have increased resistance to chemotherapeutic drugs.…”
Section: Chronic Lymphocytic Leukemiamentioning
confidence: 99%
“…In follicular lymphomas and in a fraction of diffuse B-cell lymphomas, the mechanism of B-cell leukemia/lymphoma 2 gene (Bcl-2) activation was found to be the translocation t(14;18) (q32;q21), which places Bcl-2 gene under the control of immunoglobulin heavy chain enhancers, resulting in deregulated expression of the gene (Tsujimoto et al, 1984(Tsujimoto et al, , 1985. In the most frequent adult leukemia in the Western world, the B-cell chronic lymphocytic leukemia (CLL) (Chiorazzi et al, 2005), the malignant, mostly nondividing, B cells of CLL overexpress BCL2 protein (Kitada et al, 1998). However, with the exception of less than 5% of cases in which Bcl-2 is juxtaposed to immunoglobulin loci (Adachi et al, 1990), no mechanism was discovered to explain BCL2 deregulation in CLL.…”
Section: For Several Chromosomal Abnormalities No Culprit Protein Codmentioning
confidence: 99%